2018
DOI: 10.1097/ajp.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as a Distraction Intervention to Relieve Pain and Distress During Medical Procedures

Abstract: Despite these promising results, future long-term randomized controlled trials with larger sample sizes and evaluating not only self-report measures but also physiological variables are needed. Further studies are also required both to establish predictive factors to select patients who can benefit from VR distraction and to design hardware/software systems tailored to the specific needs of different patients and able to provide the greatest distraction at the lowest cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
218
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 278 publications
(238 citation statements)
references
References 122 publications
8
218
2
10
Order By: Relevance
“…Results from the VRSQ showed that all symptoms occurred with a frequency < 20%, which has been considered negligible by the authors of the scale (Ames et al, 2005), except a slight difficulty in concentrating (21.4%). In line with previous observations (Indovina et al, 2018), nausea was very infrequent and mild. Although occurring very infrequently, some symptoms were evaluated by the participants as severe.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Results from the VRSQ showed that all symptoms occurred with a frequency < 20%, which has been considered negligible by the authors of the scale (Ames et al, 2005), except a slight difficulty in concentrating (21.4%). In line with previous observations (Indovina et al, 2018), nausea was very infrequent and mild. Although occurring very infrequently, some symptoms were evaluated by the participants as severe.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, a concern regarding the use of VR during medical procedures is that it could lose efficacy over several sessions since individuals might habituate to it. This remains to be assessed, although some encouraging data showed that the benefits of the VR distraction intervention were not lost across at least three sessions, thus suggesting that VR effects are not ascribable only to the experience novelty (Indovina et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations